If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -7) = 90 Reorder the terms: 4(-7 + x) = 90 (-7 * 4 + x * 4) = 90 (-28 + 4x) = 90 Solving -28 + 4x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '28' to each side of the equation. -28 + 28 + 4x = 90 + 28 Combine like terms: -28 + 28 = 0 0 + 4x = 90 + 28 4x = 90 + 28 Combine like terms: 90 + 28 = 118 4x = 118 Divide each side by '4'. x = 29.5 Simplifying x = 29.5
| (5x-44)=(2x) | | (5x+30y)-(-5x-10y)= | | x-40=-8 | | 4(x+1)=2(x-2) | | g(x)=F(4+x) | | 467.1=1/3*81 | | 8x+43= | | t+(10-4)=20 | | 5x-6+7=5x | | 7w/3=14 | | 467.1=1/3*81*h | | 0x+3y-7=0 | | 5x-4=-50 | | (2x-7)+(3x-34)=180 | | A=1/2bh,h | | 0.5x+4=1.2x-3 | | h(5x)=2x^2-7 | | 7/8x-9/8=2 | | 3x+5-x=2x | | 5x-(5-x)=6x | | 3/x-1=3 | | 512^-4/3 | | 224-x=-16 | | 6x=7x^2+9x-54 | | 5(x-3)-3x+7=9 | | 4/3x3.14x1.75^3 | | 5x+1+2(x+3)=4(2x+5) | | x^3+x^2-2x+72=0 | | 5x-(2x+3)=2x-(x+1) | | 20.2(x+5)-5x=1 | | -5u=15/2 | | 7x+x-5x=21-12 |